The Vice Presidential home state advantage reconsidered : analyzing the interactive effect of home state population and political experience, 1884-2008 - Devine, Christopher J.; Kopko, Kyle C. (2011)
Contiene bibliografía
Keywords: Elecciones presidenciales; Vicepresidente del Gobierno; Candidato; 1884-2008; Estados Unidos